Making Healthcare Green The Role of Cloud, Green IT, and Data Science to Reduce Healthcare Costs and Combat Climate Change - Godbole, Nina S. (Springer International Publishing, 2018)
This book offers examples of how data science, big data, analytics, and cloud technology can be used in healthcare to significantly improve a hospital's IT Energy Efficiency along with information on the best ways to improve energy efficiency for healthcare in a cost effective manner. The book builds on the work done in other sectors (mainly data centers) in effectively measuring and improving IT energy efficiency and includes case studies illustrating power and cooling requirements within Green Healthcare. Making Healthcare Green will appeal to professionals and researchers working in the areas of analytics and energy efficiency within the healthcare fields.